2020
DOI: 10.1007/s00580-020-03170-4
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic kidney disease concurrent with feline parvovirus and bacterial infections in domestic shorthair cat: a case report

Abstract: Feline polycystic kidney disease (PKD) is an inherited disorder caused by the mutation of PKD1 gene that eventually lead to the development of chronic kidney disease. The latter condition causes hypertension and eventually progress into congestive heart failure. Feline parvovirus (FPV) is a highly contagious and often fatal disease infecting cats and other members of Felidae. An 8-month-old female domestic shorthair cat was presented with complaint of wound dehiscence a day after ovarian hysterectomy procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…The progressive development of PKD depends on individual cats; kittens with severe cyst involvement may die at eight weeks due to kidney failure. PKD is one of the causes of the development of CKD in cats, which causes deterioration of glomerular filtration rate and metabolic waste excretion (Lam et al, 2020). In this study, the veterinarian observed irregular contours and increased volume of both left and right kidneys on palpation.…”
Section: Discussionmentioning
confidence: 57%
“…The progressive development of PKD depends on individual cats; kittens with severe cyst involvement may die at eight weeks due to kidney failure. PKD is one of the causes of the development of CKD in cats, which causes deterioration of glomerular filtration rate and metabolic waste excretion (Lam et al, 2020). In this study, the veterinarian observed irregular contours and increased volume of both left and right kidneys on palpation.…”
Section: Discussionmentioning
confidence: 57%